2021
DOI: 10.1021/acsomega.1c05451
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric Property Enhancement of PZT/Poly(vinylidenefluoride-co-trifluoroethylene) Hybrid Films for Flexible Piezoelectric Energy Harvesters

Abstract: In this study, lead zirconate titanate (PZT) ceramic particles were added for further improvement. PZT belongs to the perovskite family and exhibits good piezoelectricity. Thus, it was added in this experiment to enhance the piezoelectric response of the poly(vinylidenefluoride- co -trifluoroethylene) (PVDF-TrFE) copolymer, which produced a voltage output of 1.958 V under a cyclic pressure of 290 N. In addition, to further disperse the PZT particles in the PVDF-TrFE matrix, tetradecylpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 61 publications
(84 reference statements)
2
9
0
Order By: Relevance
“…For TS-NG, the peaks at 40 and 46°corresponding to the β-phase of P(VDF−TrFE) show an increase in the relative peak intensity after two-step polarizing, indicating the enhancement of the β-phase of P(VDF−TrFE) in the composite film. 38 The β-phase proportion is assessed to be 85.8, 91.8, and 89.7% for NG, S-NG, and TS-NG, respectively, based on FT-IR (Figure 2b) and eq S1 (Supporting Information). This result indicates that the two-step polarizing has little impact on the stabilization of the β-phase of P(VDF−TrFE).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For TS-NG, the peaks at 40 and 46°corresponding to the β-phase of P(VDF−TrFE) show an increase in the relative peak intensity after two-step polarizing, indicating the enhancement of the β-phase of P(VDF−TrFE) in the composite film. 38 The β-phase proportion is assessed to be 85.8, 91.8, and 89.7% for NG, S-NG, and TS-NG, respectively, based on FT-IR (Figure 2b) and eq S1 (Supporting Information). This result indicates that the two-step polarizing has little impact on the stabilization of the β-phase of P(VDF−TrFE).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The XRD patterns shown in Figure a show that all three composite films consist of crystalline P­(VDF–TrFE) and BaTiO 3 . , Specifically, the intensities of all diffraction peaks of composite films increase after simultaneous polarizing and two-step polarizing, implying that P­(VDF–TrFE) and BaTiO 3 crystallize from the nonpolar phase to the polar phase, respectively. For TS-NG, the peaks at 40 and 46° corresponding to the β-phase of P­(VDF–TrFE) show an increase in the relative peak intensity after two-step polarizing, indicating the enhancement of the β-phase of P­(VDF–TrFE) in the composite film . The β-phase proportion is assessed to be 85.8, 91.8, and 89.7% for NG, S-NG, and TS-NG, respectively, based on FT-IR (Figure b) and eq S1 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…† Table 3 compares the electrical output and the efficiency of the present PENG with earlier reports. Based on the comparison, it is concluded that the fabrication of PZT and PENG devices using the doctor blade technique is relatively simple and cheaper compared to other methods like freeze casting, 6 3D-printing, 30 interdigital electrodes, 31 screen printing, 32 sputtering, 33 chemical vapour deposition (CVD), PLD, 34 spin coating, 35 solution casting 36 and electrospinning. 37 As a result of the above findings, the proposed PENG with a PZT/MWCNT/PVP composite can be used as a wearable device in self-driven physical activity applications like sensors and energy harvesters for detecting human body movements.…”
Section: Device Resultsmentioning
confidence: 99%
“…However, despite the high β-phase concentrations of PVDF and its copolymers, their low piezoelectric coefficients (d 33 values) prevent their application in piezoelectric sensors for wearable electronics. Therefore, inorganic materials, such as lead zirconium titanate (PZT) and barium titanate (BTO), have been employed to fabricate high-performance piezoelectric composites [ 34 , 35 , 36 , 37 ]. However, inorganic nanoparticles are unsuitable for fabricating flexible and high-performance piezoelectric nanogenerators (PENGs) because of their easy agglomeration due to their large surface area and high surface activity [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%